Sistem Informasi Pelayanan Pelanggan Secara Digital Pada PT. Asabri Kantor Cabang Medan - Khodijah, Siti; Syahriza, Rahmi (Universitas Labuhanbatu, 2021)
This study aims to find out how digital customer service is at PT ASABRI Medan Branch Office. This research is a measurement to determine the service information system digitally at PT. Asabri Medan Branch Office. Research data obtained from interviews with the authorities. The analytical method used in this study is a qualitative descriptive method, namely the method by accumulating data, compiled and interpreted so as to provide a true representation of the digital customer service information system at PT. Asabri Medan Branch. With the results of the study showing that the digital customer service system is very influential and very much needed at PT. Asabri Medan Branch Office, can be obtained and can be seen in the service system procedures of PT. Asabri Medan Branch Office. The conclusion from the research that PT. Asabri Medan Branch Office, in the service system procedures for TNI Soldiers, POLRI Members, PNS Kemhan and Polri providing waivers in their services based on procedures that can be accounted for, the company hopes to achieve these goals and to achieve them, service improvements are needed, namely online services through Asabri Mobile.